Pengaruh Ekspektasi Pendapatan, Pendidikan Berwirausaha dan Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa - Aldrian Syafril Lubis; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to determine the influence of Income Expectations, Entrepreneurship Education, and Family Environment on students' Entrepreneurial Interests. The research method used is a quantitative approach. The research sample consisted of students from various universities taken randomly (Random Sampling). The maximum number of respondents obtained was 200 people. Data analysis was carried out using an outer model (Outer Model) which includes calculations of Convergent Reliability, Discriminant Validity, Composite Reliability, Cronbach's Alpha, as well as an inner model (Inner Model) which involves calculating T, R-Square and f-Square statistics. For data analysis, the SmartPLS (Partial Least Square) tool version 4.0.9.3 was used. The research results show that Income Expectations (X1) have a positive and significant influence on Entrepreneurial Interest (Y). Entrepreneurship Education (X2) also has a positive influence on Entrepreneurship Interest (Y), while Family Environment (X3) has a positive and significant influence on Entrepreneurship Interest (Y). Apart from that, together, Income Expectations, Entrepreneurship Education and Family Environment have a positive and significant effect on Students' Entrepreneurial Interest.